Islet/stem cell transplantation - what's new? - Spiliotis, I; Johnson, P (Elsevier, 2017)
Type 1 diabetes mellitus (T1DM) affects 345,000 children and adults in the UK and a proportion of these patients develop hypoglycaemia unawareness. This often results in life-threatening episodes of severe hypoglycaemia. Transplantation of isolated islets of Langerhans is a minimally invasive procedure that can restore hypoglycaemia awareness in the majority of patients and has huge potential for reversing T1DM. However, it is not currently available for treating children due to the requirement for life-long immunosuppression. This review will focus on the current practice of islet transplantation in the UK, as well as the challenges and recent developments in the field. These include optimising pancreas procurement and islet isolation, improving post-transplant islet engraftment and survival, and the use of renewable sources of islets such as stem cells. It will also discuss the novel strategies being developed to enable immunosuppression-free islet transplantation. The ultimate aim is to be able to offer this technology to young people soon after diagnosis, and thereby provide a safe and sustainable "cure" for T1DM.